Estudio de factibilidad para la creación de una empresa dedicada al reciclaje de llantas usadas para la fabricación de suelas para calzado en el departamento del Quindío (2015)
This thesis is conducting a feasibility study for the creation of a used tire recycling company in the department of Quindío, with the resulting raw material is wished to produce rubber soles for shoes, This project will be supported by performing the following studies: market, technical, organizational, legal, environmental and financial aspects. Market research is based on the application of a survey of possible suppliers which will determine the quantity of used tires available; then, another survey is applied to determine the effective demand for soles and whether it can cover the demand required. The technical study details the processes required to obtain soles from recycled tires, describes all the needs and specifications required for the product. The legal and organizational aspects for the creation and operation of the establishment are also discussed, as the environmental impact that would bring the project implementation. Finally, the financial analysis includes the investments required for the implementation of the company and the main indicators of profitability are analyzed. Additionally, conclusions are exposed and pose some recommendations on this study and the feasibility or not you can have running this type of project.